2000
DOI: 10.1080/00224540009600487
|View full text |Cite
|
Sign up to set email alerts
|

A Multicultural Study of Stereotyping in English-Speaking Countries

Abstract: Citizens of 9 different English-speaking countries (N = 619) evaluated the average, or typical, citizen of 5 English-speaking countries (Great Britain, Canada, Nigeria, United States, Australia) on 9 pairs of bipolar adjectives. Participants were drawn from Australia, Botswana, Canada, Kenya, Nigeria, South Africa, the United States, Zambia, and Zimbabwe. There were statistically significant similarities in the rankings of the 5 stimulus countries on 8 of the 9 adjective dimensions and a strong convergence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Indeed, this body of work represents the significant exception to the dearth of research at the intersection of culture and stereotyping. A substantial number of papers have documented beliefs about the characteristics of ingroups and outgroups around the world (Best & Williams, 2001;Bond, 1986;Costa, Terracciano, & McCrae, 2001;Cuddy et al, 2009;Krueger, 1996;Leach, Minescu, Poppe, & Hagendoom, 2008;Marin & Salazar, 1985;McAndrew et al, 2000;Poppe, 2001;Terracciano et al, 2005;Terracciano & McCrae, 2007;Walkey & Chung, 1996). Yet, none of these diverse studies has reported that participants were perplexed by questions about stereotypes or were unable to complete the tasks.…”
Section: The Incidence and Application Of Stereotypesmentioning
confidence: 99%
“…Indeed, this body of work represents the significant exception to the dearth of research at the intersection of culture and stereotyping. A substantial number of papers have documented beliefs about the characteristics of ingroups and outgroups around the world (Best & Williams, 2001;Bond, 1986;Costa, Terracciano, & McCrae, 2001;Cuddy et al, 2009;Krueger, 1996;Leach, Minescu, Poppe, & Hagendoom, 2008;Marin & Salazar, 1985;McAndrew et al, 2000;Poppe, 2001;Terracciano et al, 2005;Terracciano & McCrae, 2007;Walkey & Chung, 1996). Yet, none of these diverse studies has reported that participants were perplexed by questions about stereotypes or were unable to complete the tasks.…”
Section: The Incidence and Application Of Stereotypesmentioning
confidence: 99%
“…Because interacting groups share the same social reality, they are likely to possess some evaluation-free, descriptive information about each other. A group's auto-stereotypes and the stereotypes held about the same group by other groups are often similar (McAndrew et al , 2000;Peabody, 1985). However, this is not the case when one group has little knowledge about another group -that is, when the group being judged and the judges themselves do not share the same reality.…”
Section: Introductionmentioning
confidence: 99%
“…These groups include Americans and Hong Kong Chinese (Bond, 1986), Latin Americans (Marín & Salazar, 1985), residents of English-speaking countries (McAndrew et al, 2000), Western Europeans (Koomen & Bähler, 1996), and Eastern Europeans (Poppe, 2001), among others. In these studies, members of each cultural group described their ingroup and the relevant outgroup(s) in terms of personality traits.…”
Section: Culture and Stereotypingmentioning
confidence: 99%